Bibliometric analysis of local wisdom-based learning: Direction for future history education research - Ulul Azmi Muhammad; Muhammad Fuad; Farida Ariyani; Edi Suyanto (Institute of Advanced Engineering and Science, 2022)
The various cultures that have entered Indonesia country make national identity and character must be strengthened by involving local wisdom in the learning activity. This study provided the bibliometric and bibliographic review of many qualified literatures about local wisdom-based learning. A bibliometric analysis was employed to conduct this study supported by some software such as VOSviewer and Publish or Perish (PoP). There were 173 documents from Scopus database published in 2012–2021 involved in this study. Results revealed that publication trends on local wisdom-based learning increased slightly from 2012 to 2020, while the development of number of citations tended to be fluctuated in the period of 2012–2021. In addition, the influential papers about local wisdom-based learning were published by most of Indonesian researchers. The trending research on local wisdom-based learning was the development of local wisdom-based teaching materials in science or physics learning to educate Indonesian elementary students’ character in which ethno-medicine-based science learning was the newly trending research. This study provides information for researchers in history education that studies related to the development of local wisdom-based historical teaching materials and the use of these teaching materials in the implementation of history learning seem like not much have been conducted in which it is expected to reinforce students’ national identity and character.